Assessment of liver fibrosis in rats by MRI with apparent diffusion coefficient and T1 relaxation time in the rotating frame. Issue 5 (26th October 2015) - Hu, Genwen; Zhang, Xuhui; Liang, Wen; Zhong, Xing; Chan, Queenie; Lin, Xiaoying; Lin, Ting; Li, Yufa; Quan, Xianyue
Abstract : Purpose: To explore the value of T 1 relaxation times in the rotating frame ( T 1 ρ or T 1 rho) for evaluating liver fibrosis stage, compared to apparent diffusion coefficients (ADCs). Materials and Methods: Liver fibrosis in model rats ( n  = 50) was produced by carbon tetrachloride (CCl4 ) injection. Five rats died during the experiment. Surviving model rats ( n  = 45) and controls ( n  = 15) were subjected to 3.0T MRI and the ADCs (b‐values: 0, 800 s/mm 2 ) and T 1 ρ values were determined. Liver fibrosis stage (F0–F4) was defined based on METAVIR scoring. Nonparametric statistical methods and receiver operating characteristic (ROC) curve analyses were employed to determine diagnostic accuracy. Results: Mean ADC and T 1 ρ associated negatively ( r  = −0.732 P  < 0.001) and positively ( r  = 0.863 P  < 0.001), respectively, with severity of fibrosis stage. Analysis of ROC curves for fibrosis staging showed that the area under the curve (AUC) for T 1 ρ (stage F0 vs. F1–F4 = 0.976, stage F0–F1 vs. F2–F4 = 0.920, stage F0–F2 vs. F3–F4 = 0.938, and stage F0–F3 vs. F4 = 0.931) was larger than that for ADCs (0.917, 0.924, 0.842, and 0.781, respectively). Conclusion: ADC and T 1 ρ values correlate with liver fibrosis stage. The performance of the T 1 ρ parameter was superior to that of the ADC parameter in the differentiation of liver fibrosis stages in a CCl4 rat model. J. Magn. Reson. Imaging 2016;43:1082–1089.